PEMIKIRAN PENDIDIKAN PROGRESIF DALAM PERSPEKTIF FAZLUR RAHMAN - Fauzi, Muhammad; Winarto, Tri (STIT Al - Ibrohimy Bangkalan, 2025)
Fazlur Rahman's thought presents a new paradigm in Islamic education, emphasizing value transformation and methodological reform. This study aims to analyze the concept of progressive education from Fazlur Rahman's perspective, with a particular focus on his double movement hermeneutical method as a pedagogical approach. The research employs a qualitative method through library research based on Rahman's primary works and academic secondary sources. The findings reveal that Rahman's progressive education emphasizes the integration of Qur’anic ethical values with modern social contexts, shaping learners to be critical, rational, and socially responsible. His concept rejects the dichotomy between religious and secular sciences and promotes contextual, reflective, and ijtihad-based learning. Rahman's thought is highly relevant to the context of Islamic education in Indonesia, particularly in supporting holistic and transformative curricula. This study recommends the integration of Rahmanian principles in curriculum design, teacher training, and educational policy to strengthen the character and competitiveness of future Muslim generations.